Association between age at onset of overweight and risk of hypertension across adulthood. Issue 9 (21st February 2022) - Li, Weijian; Fang, Wei; Huang, Zegui; Wang, Xianxuan; Cai, Zefeng; Chen, Guanzhi; Wu, Weiqiang; Chen, Zhichao; Wu, Shouling; Chen, Youren
Abstract : Objective: The aim of this study was to examine the association between age at onset of overweight and incident hypertension. Methods: We analysed 4742 participants with new-onset overweight from the Kailuan study between 2006 and 2015 and and 4742 age-matched and sex-matched controls selected randomly from the same cohort but with normal weight. Participants were compared with respect to subsequent risk of hypertension, with sub-HR calculated with the Fine and Gray model, according to age of onset of overweight. Results: Over a mean follow-up period of 5.17 years, 1642 overweight participants (34.6%) and 1293 normal-weight controls (27.3%) were subsequently diagnosed with hypertension. The median age at onset of overweight was 49.1 years. Compared with normal-weight controls, the multivariable-adjusted sub-HR for hypertension among participants with onset of overweight at 18–39 years of age, 40–49 years of age, 50–59 years of age and ≥60 years of age was 1.38 (95% CI 1.11 to 1.72), 1.27 (95% CI 1.09 to 1.49), 1.23 (95% CI 1.09 to 1.38) and 1.14 (95% CI 0.99 to 1.32), respectively. Onset of overweight in each age range was significantly associated with increased risk of hypertension, except for the group with onset at ≥60 years of age. The risk increased with each decade of attenuation of age at onset, peaking at 18–39 years of age. Conclusions: Younger age at onset of overweight across adulthood was associated with significantly increased risk of hypertension, with the highest relative risk among participants with onset of overweight at 18–39 years of age.